Optimal Algorithms for Energy Storage Systems in Microgrid Applications: An Analytical Evaluation Towards Future Directions - Reza M.S.; Rahman N.; Wali S.B.; Hannan M.A.; Ker P.J.; Rahman S.A.; Muttaqi K.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Electric energy storage; Analytical evaluation; Bibliometric; Bibliometrics analysis; Carbon emissions; Energy storage system; Microgrid; Microgrid systems; Optimal algorithm; Storage systems; Environmental impact